2022
DOI: 10.3390/app12168328
|View full text |Cite
|
Sign up to set email alerts
|

Where Are Smart Cities Heading? A Meta-Review and Guidelines for Future Research

Abstract: (1) Background: Smart cities have been gaining attention in the community, both among researchers and professionals. Although this field of study is gaining some maturity, no academic manuscript yet offers a unique holistic view of the phenomenon. In fact, the existing systematic reviews make it possible to gather solid and relevant knowledge, but still dispersed; (2) Method: through a meta-review it was possible to provide a set of data, which allows the dissemination of the main theoretical and managerial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…At the same time, recent growth in digital technologies is enabling cities to streamline smart services and offering new products [ 78 ]. This argument is also pointed out by some recent studies that have investigated the literature on DT in the context of meta-reviews Reis et al [ 73 ] or meta-synthesis [ 79 ] in smart cities. Therefore, we argue that additional efforts are needed to reduce the knowledge gap between these two concepts (sustainability and smart cities) and DT.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…At the same time, recent growth in digital technologies is enabling cities to streamline smart services and offering new products [ 78 ]. This argument is also pointed out by some recent studies that have investigated the literature on DT in the context of meta-reviews Reis et al [ 73 ] or meta-synthesis [ 79 ] in smart cities. Therefore, we argue that additional efforts are needed to reduce the knowledge gap between these two concepts (sustainability and smart cities) and DT.…”
Section: Resultsmentioning
confidence: 80%
“…[ 55 ]. These disruptive technologies have been offering unprecedented opportunities to create and develop value-added products and services [ 73 ]. In that regard, we identified that smart cities work as an extensive smart ecosystem, including different value activities and specific business functions and technologies [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then coded the phrases into categories and subcategories [52]. That is, we had to find patterns in the codes, identifying the most relevant ideas [53], allowing us to generate a map that gave us an overview of the data. Moreover, we used computer-based qualitative data analysis software (QDAS) NVIVO 12 (https://www.qsrinternational.com, accessed on 27 July 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The digital transformation has played a vital role in facilitating the adoption of Digital Twin technology in smart cities, along with other disruptive technologies, such as IoT, cloud computing, big data, cyber-physical systems, and AI [40]. By leveraging these technologies, smart cities can enhance their capacity to offer optimized services and products that address various societal challenges while prioritizing sustainability and intelligence [41,42].…”
mentioning
confidence: 99%